Associations between enroller demographics and participant enrollment into an emergency department-based cancer prevention trial - Ivana-Re Baldie; Beau Abar; Brenda Hernandez-Romero; Nancy Wood; Adrienne Morgan; David Adler (JEM Reports, 2025)
Background: Inadequate diversity among clinical trial participants threatens external validity. Potential explanations for disparities in participation include staff bias, lack of access to studies, and racial discordance between staff and patients. Objectives: We examined associations between patient and enroller demographics and enrollment into a randomized controlled trial (RCT) on cancer screening among Emergency Department (ED) patients. Enrollment through the ED ensures access to trials across a diverse patient population, and the dataset analyzed is of sufficient magnitude and diversity (both in enrollers and patients) to provide novel evaluation. Methods: Research enrollers identified potentially eligible ED patients for enrollment using the electronic health record, approached patients and described the RCT, and attempted to enroll them into the study. Results: A total of 4419 patient-enroller encounters were documented. Enrollment rates were similar across enroller gender (47 % when enroller was a woman; 48 % when enroller was a man), though there was mild variability across enroller race (50 % when enroller was White; 45 % when enroller was Asian; 44 % when enroller was Black). Concordance between patient and enroller race was not tied to enrollment. Conclusions: Conducting research in diverse settings like the ED can mitigate access barriers, as can enroller cultural competency training.